A concise synthesis of herbertenolide. Issue 11 (1st March 2022) - Hu, Jiadong; Ji, Kai; Yan, Lihong; Yang, Siyu; Li, Yin; Wen, Wen; Chen, Le; Wu, Xiaohui; Hu, Youcai; Xie, Weiqing
Abstract : A concise synthesis of (±)-herbertenolide (8 LLS) has been achieved based on H2 O2 -mediated oxidative ring contraction for forging contiguous quaternary carbon centers (CQCCs). Abstract : A concise synthesis of (±)-herbertenolide has been accomplished herein. The strategy relies on a H2 O2 -mediated oxidative ring contraction of all-substituted cyclic α-formyl ketones for the stereospecific construction of contiguous quaternary carbon centers (CQCCs). Furthermore, a Sc(OTf)3 /chiral N, N ′-dioxide catalyzed asymmetric Michael addition of benzofuranone to MVK has been optimized for forging a chiral aromatic quaternary carbon center, which enables the formal synthesis of (+)- ent -herbertenolide.